Stakeholder-informed multi-criteria decision-making for sustainable heat supply - Kaiser, Alwina; Cadenbach, Anna Marie; Krebs, Friedrich (International Journal of Sustainable Energy Planning and Management, 2025)
The heating transition presents municipalities with the challenge of integrating technical, economic, and socially acceptable aspects into the planning and implementation of climate-neutral heating systems. This paper introduces a Multi-Criteria Decision Analysis (MCDA) approach to support heat planning processes. The goal is to facilitate investment decisions by incorporating the priorities of various stakeholders and evaluating heating supply options based on a shared factual basis. At the same time, conflicts of interest are identified and addressed. The developed decision-making model consists of six steps, including the selection and weighting of criteria as well as the evaluation of alternative scenarios. The methodology was applied within the WAERMER project, supported by stakeholder participation and a prototype interactive visualization. The evaluation is based on twelve quantitative and qualitative criteria across the categories of environment, economy, technology, and social compatibility. Using a case study in an urban district of a mid-sized city in Northern Germany, scenarios were compared to identify optimal solutions for heat supply. The paper illustrates how a participatory MCDA process can support municipal heat planning by making stakeholder priorities visible and enabling transparent scenario evaluation. While implementation remains context-dependent, the structured approach lays a foundation for informed and socially accepted planning decisions.